2021
DOI: 10.3390/soc11040121
|View full text |Cite
|
Sign up to set email alerts
|

Fake News and the “Wild Wide Web”: A Study of Elementary Students’ Reliability Reasoning

Abstract: Online research presents unique challenges for elementary students as they develop and extend fundamental literacy skills to various media. Some features of internet text differ from that of traditional print, contributing to the challenges of discerning “fake news.” Readers must understand how to navigate online texts to conduct research effectively, while applying critical thinking to determine the reliability of online information. Descriptive data from an ongoing study revealed that children in grades 1–5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…On the one hand, there are several technical solutions to detect fake news on the web, such as machine learning and artificial intelligence [ 48 ]. On the other hand, internet users need to be more aware of fake news existing and possess some basic knowledge about fake news recognition [ 49 ]. Our results are in line with Trinicic et al [ 50 ] and confirm that there is some lack of competence concerning media literacy [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, there are several technical solutions to detect fake news on the web, such as machine learning and artificial intelligence [ 48 ]. On the other hand, internet users need to be more aware of fake news existing and possess some basic knowledge about fake news recognition [ 49 ]. Our results are in line with Trinicic et al [ 50 ] and confirm that there is some lack of competence concerning media literacy [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the data obtained, students scored low on the information skill component, and they still have difficulty distinguishing credible or non-credible sources (Pilgrim dan Vasinda 2021). When searching for information they only use the Google search engine (Salehudin, Marniah, dan Hariati 2020) and choose the source suggested by Google at the top.…”
Section: Development Stagementioning
confidence: 99%
“…The popularity of YouTube is especially pronounced in younger children. A 2018 survey in the United States reported that 81% of children aged 11 watched YouTube, and 34% of parents said their child watched YouTube regularly (Pew Research Center, 2018 [70]). In the United Kingdom, 95% of children aged 3-17 are reported to use video-sharing platforms (Ofcom, 2022[12]).…”
Section: Key Behaviours and Digital Activitiesmentioning
confidence: 99%
“…Parents and caregivers are vulnerable to disinformation themselves, and often come into contact with information that seems false or untrue (Pew Research Center, 2018 [70]). Even younger parents, despite being (mis)labelled as "digital natives", still struggle with the nature of the digital world (Box 1.6).…”
Section: Susceptibility To False and Misleading Contentmentioning
confidence: 99%